Physical Fitness Level of Children with Special Needs in Special Needs School - Muhamad Suma Wijaya; Julinur Hafid; Lilis Maesaroh; Rifki Rosad; Anisa Shopiani (Universitas Negeri Semarang, 2025)
This study aims to describe the physical fitness level of students with disabilities in Special Education Schools using the Harvard Step Test method. The subjects consisted of 13 students aged 11–20 years with various types of disabilities, including intellectual disability, physical disability, hearing impairment, speech disorder, autism spectrum disorder (ASD), and attention deficit hyperactivity disorder (ADHD). The test was carried out through a five-minute step-up exercise, followed by pulse measurement during the recovery phase to calculate the Fitness Index. The findings revealed that most students were in the low fitness category. A total of 76.9% of participants fell into the very poor category, 15.4% into the poor category, and only 7.7% achieved the average category, with an overall mean Fitness Index of 52.4. Variation in results was found only among students with intellectual disabilities, while students with physical disabilities, speech disorders, autism spectrum disorder, and ADHD were entirely in the very poor category. These results may be influenced by physical limitations, low levels of daily physical activity, and the lack of adaptive exercise programs in schools. The findings are consistent with recent studies that highlight the importance of structured, inclusive, and continuous physical activity programs to improve physical fitness and quality of life among students with disabilities.